2023
DOI: 10.3390/tropicalmed8010063
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasmosis: A Timeless Challenge for Pregnancy

Abstract: This study aimed to evaluate the prevalence of toxoplasmosis in pregnant women, as well as the general characteristics, clinical and laboratory findings, and pregnancy and fetal outcomes of pregnant women diagnosed with acute toxoplasma infection (ATI). The toxoplasma IgM, IgG, and IgG avidity test results of pregnant women who applied to our referral hospital between January 2016 and June 2022, and among them, those diagnosed with ATI, were analyzed. The 119 patients diagnosed with ATI during this time period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…These ndings coincided with Kazemi et al (18) who detected an abortion rate of 32% among IgG seropositive women and concluded that toxoplasma infection could be considered the most signi cant cause of abortion. Also, Çakırca et al (19) reported a prevalence and acute infection rates of toxoplasmosis of 46.2% and 4% among pregnant women with an incidence of the mother-to-child transmission rate of 5%. Further, Hassan et al (20) detected IgG seropositivity to T. gondii in 45.2% of their series of pregnant women and found the rate of seropositive women changed in ascending direction with pregnancy progress from 44.2-67.7% in the 1st and 3rd trimesters, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These ndings coincided with Kazemi et al (18) who detected an abortion rate of 32% among IgG seropositive women and concluded that toxoplasma infection could be considered the most signi cant cause of abortion. Also, Çakırca et al (19) reported a prevalence and acute infection rates of toxoplasmosis of 46.2% and 4% among pregnant women with an incidence of the mother-to-child transmission rate of 5%. Further, Hassan et al (20) detected IgG seropositivity to T. gondii in 45.2% of their series of pregnant women and found the rate of seropositive women changed in ascending direction with pregnancy progress from 44.2-67.7% in the 1st and 3rd trimesters, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30][31][32][33] The reactivation of eye infection caused by T. gondii is frequent because it is an immunologically favorable environment [26,29,31,[34][35][36] and pregnancy is a facilitating factor for its reactivation due to the immunotolerance that it confers on the host. [26,[37][38][39] The T. gondii parasite, when penetrating the human cell, activates several cytokine genes such as IL-10, IL-1β, IFN-γ, which are associated with the development of ocular toxoplasmosis. [3,33,[40][41][42] A study shows that the appearance of eye lesions is a consequence of the susceptibility of the host gene associated with exposure to more virulent strains.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that many toxoplasmosis cases are not reported or are not detected because of mild conditions or because the disease is prevalent. 12 , 13 Preliminary results showed the significant effectiveness of antibiotic therapy in preventing transmission and decreasing the severity of toxoplasmosis infections; however, not all studies have supported such dramatic improvement. 14 Postnatal vaccination is acknowledged to be an effective approach for the prevention of congenital rubella syndrome.…”
Section: Discussionmentioning
confidence: 99%